2011
DOI: 10.1590/s0037-86822011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma cruzi antibodies and inflammatory markers in uncompensated heart failure

Abstract: Introduction: Heart failure (HF) represents the final stage of chronic chagasic cardiomyopathy (CChC). The diagnosis of CChC is based on the demonstration of anti-Trypanosoma cruzi antibodies (aTcAg) and clinical and epidemiological data. In Venezuela, there are no data about the prevalence of chagasic HF. The aim of this study was to determine the epidemiological, clinical, and inflammatory risk factors associated with seronegative or seropositive HF patients. Methods: We performed a cross-sectional study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…However, CRP is a nonspecific marker of inflammation that noticeably rises in advanced stages of heart disease, disregarding the etiology. This was demonstrated by BRAVO et al (2010) 5 , who reported that CRP levels are elevated in patients with decompensated heart failure. They found no statistically significant differences between patients with serum antibodies for T. cruzi and seronegative patients, notwithstanding, they found that CRP levels were significantly higher in patients in class IV of New York Heart Association functional classification (NYHA IV) when compared with patients in NYHA III, indicating that the CRP serum levels are associated with the severity of the cardiac pathology.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, CRP is a nonspecific marker of inflammation that noticeably rises in advanced stages of heart disease, disregarding the etiology. This was demonstrated by BRAVO et al (2010) 5 , who reported that CRP levels are elevated in patients with decompensated heart failure. They found no statistically significant differences between patients with serum antibodies for T. cruzi and seronegative patients, notwithstanding, they found that CRP levels were significantly higher in patients in class IV of New York Heart Association functional classification (NYHA IV) when compared with patients in NYHA III, indicating that the CRP serum levels are associated with the severity of the cardiac pathology.…”
Section: Discussionmentioning
confidence: 70%
“…The increased serum levels of CRP reflect a vascular inflammation state and they are associated with the development of cardiovascular events 4 . Increased levels of serum CRP have been reported in advanced clinical stages of Chagas cardiomyopathy 2 , 18 , 21 , however, this increase was similarly observed in non-chagasic cardiomyopathy 5 .…”
Section: Introductionmentioning
confidence: 89%
“…Por esta razón, además del grupo de controles sanos, en el presente estudio se incluyeron de forma exploratoria otros grupos de control: a) individuos con factores de riesgo, quienes por vivir o haber vivido en áreas endémicas pueden desarrollar respuesta inmune específica tanto humoral como celular contra el parásito (43); b) individuos infectados con Leishmania, parásito que al igual que T. cruzi pertenece a la familia Trypanosomatidae, y comparte con este algunos de sus epítopos (44,45), y c) individuos con enfermedad cardiaca no infectados, quienes por presentar inflamación o por residir en áreas endémicas pueden tener un ruido de fondo mayor que el de los controles sanos sin estas características (46,47). Los resultados obtenidos indican que si bien estos individuos de control presentaron valores de absorbancia similares a los del grupo de individuos sanos, en la mayoría de los casos se pudo discriminar entre individuos infectados y no infectados.…”
Section: Discussionunclassified
“…The 27 studies included in this meta-analysis adopted various study designs. The majority were prospective cohort (n = 12; 44%) [161,170,174,220,222,227,229,[231][232][233]235,236] followed by cross- sectional studies (n = 11; 41%) [214][215][216][217][218][219]221,223,226,228,230] and retrospective cohort (n = 4; 14%) [171,224,225,234]. The greater majority (n = 22; 77%) investigated Chagasic CM due to T. cruzi infection and the remaining 23% investigated malaria CM due to Plasmodium infection [161,170,171,174,236].…”
Section: Study Characteristicsmentioning
confidence: 99%